Protocols for protection of human participants: A comparison of five countries - Clough, Bonnie A. (Animo Repository, 2013)
Research ethics protocols relating to human participants were compared across five countries, namely, Australia, Azerbaijan, Iran, the Philippines, and South Africa. These countries were considered to be geographically and culturally diverse, as well as representing both developed and developing countries. The extent to which the research participant is protected across cultures and countries was investigated, with particular focus on the use of informed consent procedures. It was argued that current ethical guidelines and practices fail to ensure the protection of the most vulnerable participants within these cultures. Informed consent mechanisms also often fail to consider cultural differences in self-concept, understanding of research methods, and power differences between researchers and participants. Discussion of these ethical challenges and recommendations for research ethics development within these cultures and countries are discussed. © 2013 by joan sieber.